Interferon-Gamma at the Crossroads of Tumor Immune Surveillance or Evasion - Castro, Flávia; Cardoso, Ana Patrícia; Gonçalves, Raquel Madeira; Serre, Karine; Oliveira, Maria José (Frontiers in Immunology, 2018)
Interferon-gamma (IFN-γ) is a pleiotropic molecule with associated antiproliferative, pro-apoptotic and antitumor mechanisms. This effector cytokine, often considered as a major effector of immunity, has been used in the treatment of several diseases, despite its adverse effects. Although broad evidence implicating IFN-γ in tumor immunosurveillance, IFN-γ-based therapies undergoing clinical trials have been of limited success. In fact, recent reports suggested that it may also play a protumorigenic role, namely through IFN-γ signaling insensitivity, downregulation of major histocompatibility complexes and upregulation of indoleamine 2,3-dioxygenase (IDO) and of checkpoint inhibitors, as programmed cell-death ligand 1 (PD-L1). However, the IFN-γ-mediated responses are still positively associated with patient’s survival in several cancers. Consequently, major research efforts are required to understand the immune contexture in which IFN-γ induces its intricate and highly regulated effects in the tumor microenvironment. This review discusses the current knowledge on the pro and antitumorigenic effects of IFN-γ as part of the complex immune response to cancer, highlighting the relevance to identify IFN-γ responsive patients for the improvement of therapies that exploit associated signaling pathways.